THE HISTORY OF Wanha’ - Burelo Ramos, Carlos Manuel; López Dobrusin, Eva; Morales Rodríguez, Neil Ebeth Meled; Rosales Rosado, Susana; Ascencio Rivera , Jesús Manuel; Cardeño Resendis, Judith Paola (Kuxulkab’, 2024)
This paper attempts to present the events that occurred to achieve the declaration of the Wanha’ Biosphere Reserve in the state of Tabasco in 2023. This reserve has a wide biodiversity, most of it still unknown, but its main and best-known value is the inland mangroves present on the banks of the San Pedro Mártir River, which grow in fresh water and are the most inland mangroves on the planet. The text is divided into chapters that represent significant stages in the history of its creation, also highlighting the development of research work and reforestation efforts that have been made in the area. It concludes with a vision for the future, mentioning the perspectives of possible studies that enrich the knowledge of the biodiversity and importance of the place, as well as the monitoring of reforestation work for the purpose of conservation.